2022
DOI: 10.1021/acs.langmuir.1c03289
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Hydrothermal Synthesized Nitrogen and Sulfur Codoped Carbon Dots for Acid Corrosion Inhibition of Q235 Steel

Abstract: N and S codoped carbon dots having good water solubility have been successfully made by a novel hydrothermal method and characterized by FTIR, XPS, and TEM. The as-synthesized CDs were carbon particles rich in polar functional groups less than 10 nm in size. Electrochemical measurements, gravimetry, and surface analysis methods were utilized to examine the inhibition characteristics and adsorption mechanism of CDs on the carbon steel in acid pickling solutions. Electrochemical measurements verified that the CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…It is well known that surface defects introduced by N and S co-doping affect the graphitization degree of CDs. 30,33 Experiments showed that the GCDs and GCDs-starch prepared in this study exhibited strong uorescence, and our GCDs-starch powder formed a high contrast with the background for LFP detection.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…It is well known that surface defects introduced by N and S co-doping affect the graphitization degree of CDs. 30,33 Experiments showed that the GCDs and GCDs-starch prepared in this study exhibited strong uorescence, and our GCDs-starch powder formed a high contrast with the background for LFP detection.…”
Section: Resultsmentioning
confidence: 73%
“…6) showed stretching vibrations for O–H at 3383 cm −1 , C–H at 2919 cm −1 , CC/CO at 1594 cm −1 , N–H at 1455 cm −1 , C–N at 1400 cm −1 , C–S at 1472 cm −1 , SO at 1475 cm −1 , and C–O at 1300 cm −1 . 28,30–33 These peaks were also observed in the FTIR spectrum of GCDs-starch, which combined the FTIR peaks for starch, GCDs-starch powder, and GCDs and indicated that GCDs were wrapped around the starch granules (Fig. 6).…”
Section: Resultsmentioning
confidence: 81%
“…Remarkably, the resultant CDs exhibited a prominent inhibition efficiency of 96% at 100 mg L −1 . 17 Thereafter, Yang, 24 Ye, 25 Luo, 26 He, 22 Zhang, 28 Chen, 18 Yadav, 19 Ye, 20 Cui, 23 Guo, 21 Zhang 27 et al adopted ionic liquid-functionalized CDs, N-doped CDs or N, S co-doped CDs as corrosion inhibitors for carbon steel, copper or aluminium alloy in a salt solution or acid solution. Almost all the CDs exhibited an excellent corrosion inhibition efficiency of more than 90% even at low concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Fortunately, in recent years, CDs have also been used as a novel and green corrosion inhibitor, and they exhibited remarkable corrosion inhibitory actions for multiple metals in acid corrosive solution. [17][18][19][20][21][22][23][24][25][26][27][28] For instance, Zhao's group obtained CDs from 4-aminosalicylic acid via solvothermal treatment and used them as an efficient corrosion inhibitor for carbon steel in acid solution. Remarkably, the resultant CDs exhibited a prominent inhibition efficiency of 96% at 100 mg L −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation